Natural Products in Chemical Biology. Herausgegeben von Natanya Civjan. (19th March 2013) - Süssmuth, Roderich D.
<x xml:space="preserve">Abstract</x> John Wiley & Sons, Hoboken, 2012. 436 S., geb., 100.20 €.—ISBN 978‐1118101179<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>